Analisa Kemampuan Guru Mata Pelajaran Bahasa Indonesia dalam Penyusunan dan Penggunaan Lembar Kerja Siswa (LKS) berbasis Kurikulum Merdeka di SMK Muhammadiyah 1 Palu - Andi Bismawati; Nur Halifah (Universitas Tadulako, 2022)
The newly implemented Independent Curriculum in the learning process requires students to play an active and independent role in learning. Teachers as facilitators must be able to choose good learning resources for their students to use, one of which is selecting student worksheets. The teacher must carry out an analysis of the needs of learning resources in learning. The purpose of this study was to determine the teacher's ability to compile and use student worksheet in Informatics learning in the material of Computer Networks and the Internet in class X SMK Muhammadiyah 1 Palu. This type of research is qualitative descriptive research. The results of this study show that the ability of Indonesian teachers in compiling student worksheet according to the Independent Curriculum obtains an average score of 81% in the very good category and the ability to use use prepared student worksheet to obtain an average score of 89% in the very good category.